2020
DOI: 10.3389/fonc.2020.00828
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal Myxoid Chondrosarcoma: Clinical and Molecular Characteristics and Outcomes of Patients Treated at Two Institutions

Abstract: Background: Extraskeletal myxoid chondrosarcoma (EMC) is a rare subtype of STS, which usually arises in extremities. It carries reciprocal translocations involving the NR4A3 gene. It displays an indolent behavior, but studies with long follow-up showed a high proportion of local and distant recurrences. For patients with progressing metastatic disease anthracycline-based chemotherapy is the standard front-line regimen, though has limited activity. There is some evidence on possible activity of antiangiogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Hemorrhagic and necrotic degeneration can also be found and signal characteristics in T1-weighted MR vary accordingly, from low- to intermediate- and high-intensity signals [ 11 , 12 , 13 ]. Metastases are usually pulmonary, however, extra-pulmonary metastases can occur, with lymph node involvements seen more often than in other soft tissue sarcoma (STS) subtypes [ 14 , 15 ].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Hemorrhagic and necrotic degeneration can also be found and signal characteristics in T1-weighted MR vary accordingly, from low- to intermediate- and high-intensity signals [ 11 , 12 , 13 ]. Metastases are usually pulmonary, however, extra-pulmonary metastases can occur, with lymph node involvements seen more often than in other soft tissue sarcoma (STS) subtypes [ 14 , 15 ].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Extraskeletal myxoid chondrosarcoma can develop distant metastasis, similar to other STS. The most common metastasis site is the lung, although lymph node metastases are seen more often in EMC than in other STS sub-types [ 15 , 16 ]. Recurrent or metastatic STS is treated using a standard palliative EBRT regimen (for example, 30 Gy/10 frac-tions, 20 Gy/5 fractions, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…EMC was a low-grade malignancy primary affecting the limbs and limb girdles while seldomly affecting the foot, with 5-years, 10-years, and 15-years survival rates of 82–90%, 65–70%, and 58–60%, respectively ( Meis-Kindblom et al, 1999 ; Stacchiotti et al, 2020 ). Despite the indolent behavior and a long clinical course, EMC has a high rate of local recurrences and distant metastasis ( Chiusole et al, 2020 ). Here we report a rare EMC deriving from the foot, which developed aggressive during the clinical course with recurrences and multiple metastases ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This neoplasm is always described as low-grade tumor because it has an indolent course throughout the prolonged natural history. Nevertheless, recent studies revealed that EMC may be a more aggressive malignant tumor neoplasm owing to the high rate of local recurrence and distant metastasis even after radical resection ( Meis-Kindblom et al, 1999 ; Hisaoka and Hashimoto, 2005 ; Chiusole et al, 2020 ). For patients with repeated recurrences, the interval between recurrences was gradually shortened, suggesting that the EMC may become more invasive after relapsed ( Paioli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation